Innovative Technologies in Information Warfare as a Means of Protecting National Interests of Ukraine and Georgia: A Literature Review - Derviş, Leyla (Asian Journal of Interdisciplinary Research, 2025)
Information wars are becoming increasingly important in modern conflicts, posing a serious threat to national security. Disinformation and cyber-attacks are an important element of the hybrid aggression of the Russian Federation, which Ukraine and Georgia have encountered. The article aims to identify the leading innovative technologies that contribute to the conduct of information warfare. The study is based on a content analysis of 34 scientific publications selected from Google Scholar, Scopus and Web of Science databases for the period from 1995 to the present. Key words such as “information warfare”, “cyber-attacks”, “Ukraine”, “Georgia” and “national security” were used. Systematic and comparative methods were used to identify common and distinctive features in strategies to counter information threats. The results determined that the experience of Ukraine and Georgia offers valuable information about the dynamics of information warfare and its consequences for national security. Among the leading technologies used in hybrid warfare are artificial intelligence, social networks, deepfakes, bots, and cyber-attacks. Despite these challenges, both countries have taken steps to counter Russian influence and strengthen their resistance to disinformation. The experience of Ukraine and Georgia emphasizes the importance of countering information warfare in national security strategies. The findings showed that legislative, regulatory and technological measures are critical to mitigating the impact of disinformation campaigns and protecting democratic institutions.